Physiological, psychosocial, and environmental factors in depression among autistic girls. Issue 6 (19th July 2021) - Sharpley, Christopher F.; Bitsika, Vicki; McMillan, Mary E.; Agnew, Linda L.
Abstract: Autism Spectrum Disorder and depression are often co‐occurring in young people. However, despite the association between these two disorders, and the fact that females have a higher prevalence of depression than males in the general population, there is little reported evidence regarding the correlates of depression in young autistic females. Several physiological (age, menarche, HPA‐axis responses), psychological (social anxiety), and environmental or genetic (mothers' depression) factors were tested for their contribution to depression severity in a sample of 53 autistic girls aged 6 yr to 17 yr. Depression scores were collected from the girls' self‐ratings and also from the ratings their mothers gave them. Regression results indicated that girls' social anxiety, age, and mothers' depression were common significant contributors to both sets of depression scores, but with different effects. Autistic girls' self‐reports of their depression were significantly associated with their HPA‐axis responses but not with their menarche status. Implications for research and clinical settings are discussed.